2000
DOI: 10.1002/(sici)1097-4652(200004)183:1<74::aid-jcp9>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Human three-dimensional fibroblast cultures express angiogenic activity

Abstract: Human neonatal fibroblasts were cultured on a lactate-glycollate copolymer scaffold for 12-16 days to form a three-dimensional dermal equivalent tissue. The cellular content of vascular endothelial growth factor (VEGF) mRNA in these three-dimensional cultures was 22-fold greater than that observed in the same fibroblasts grown as monolayers. No induction was shown by hepatocyte growth factor (HGF) or angiopoietin 1 indicating that the effect was specific to VEGF. The predominant VEGF splice variant, detected b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
50
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 40 publications
3
50
0
Order By: Relevance
“…This conclusion is supported by previous work in which the angiogenic capacity of 3DFC material has been demonstrated by in vitro tests of endothelial cell proliferation and ␣ v ␤ 3 integrin induction, 27 new vessel outgrowth and human vascular endothelial cell motility in rat aortic ring assays, 28 and use of in vivo tests of the chick chorioallantoic membrane. 27 Additional clinical studies to assess the healing of diabetic foot ulcers 29 after treatment with allogeneic, viable 3DFC material have further demonstrated the angiogenic ability of this tissue-engineered material in subjects with functional immune systems and suggest that viable 3DFC maintains its angiogenic effect with a negligible host immune response. Therefore, in light of the previously reported angiogenesis data in both in vitro and in vivo models, we anticipated that an angiogenic effect in an immune-incompetent animal similar to that seen in studies in immune-competent, allogeneic humans would take place and that angiogenic effects of viable 3DFC would be functional in other tissues, including damaged myocardium of the heart.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This conclusion is supported by previous work in which the angiogenic capacity of 3DFC material has been demonstrated by in vitro tests of endothelial cell proliferation and ␣ v ␤ 3 integrin induction, 27 new vessel outgrowth and human vascular endothelial cell motility in rat aortic ring assays, 28 and use of in vivo tests of the chick chorioallantoic membrane. 27 Additional clinical studies to assess the healing of diabetic foot ulcers 29 after treatment with allogeneic, viable 3DFC material have further demonstrated the angiogenic ability of this tissue-engineered material in subjects with functional immune systems and suggest that viable 3DFC maintains its angiogenic effect with a negligible host immune response. Therefore, in light of the previously reported angiogenesis data in both in vitro and in vivo models, we anticipated that an angiogenic effect in an immune-incompetent animal similar to that seen in studies in immune-competent, allogeneic humans would take place and that angiogenic effects of viable 3DFC would be functional in other tissues, including damaged myocardium of the heart.…”
Section: Discussionsupporting
confidence: 81%
“…8,9,12 Data from the present study suggest that the viable 3DFC material is responsible for the observed and quantified increase in new microvessels within the damaged epicardium and myocardium. This conclusion is supported by previous work in which the angiogenic capacity of 3DFC material has been demonstrated by in vitro tests of endothelial cell proliferation and ␣ v ␤ 3 integrin induction, 27 new vessel outgrowth and human vascular endothelial cell motility in rat aortic ring assays, 28 and use of in vivo tests of the chick chorioallantoic membrane. 27 Additional clinical studies to assess the healing of diabetic foot ulcers 29 after treatment with allogeneic, viable 3DFC material have further demonstrated the angiogenic ability of this tissue-engineered material in subjects with functional immune systems and suggest that viable 3DFC maintains its angiogenic effect with a negligible host immune response.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Tissue-engineered skin substitutes with epidermal and dermal components have been designed to provide the lost cellular functions of the epidermis and dermis, respectively. 7,14,15 Although dermal substitutes may provide wound coverage and reduce pain, they still require an epidermal component, which is often provided through one or more applications of split-thickness autografts, necessitating multiple surgical procedures that injure the donor site and increase scar morbidity. 16 On the other hand, cultured epithelial autografts without dermal component have shown unreliable take rate possibly owing to lack of adequate vascularization and produce an unstable epidermis that is prone to blistering or minor trauma.…”
mentioning
confidence: 99%
“…Several polymeric or natural biomaterials can be employed as dermal substrates, including fibroblast-containing nylon, 7 fibroblast-containing biodegradable polyglactin matrix, 15,18 collagen/chondroitin-6-sulfate composite (Integra), [19][20][21] and decellularized dermis (Alloderm/Xenoderm). 22,23 However, vascularization of the dermal support remains a major challenge limiting the survival and take rate of the multilayered epithelial component.…”
mentioning
confidence: 99%